Impact of foxes digging for the pygmy bluetongue lizard (Tiliqua adelaidensis). Issue 2 (2nd July 2016) - Nielsen, Torben P.; Bull, C. Michael
ABSTRACT: The endangered pygmy bluetongue lizard ( Tiliqua adelaidensis ) is endemic to heavily fragmented patches of native grassland in the mid-north region of South Australia. The lizards live in spider burrows, and suitable burrows can be a limiting factor to local populations. The invasive red fox ( Vulpes vulpes ) is a likely predator of the lizards. No previous research has focussed on the effects of foxes on pygmy bluetongue lizards. This article presents observations from three sampling rounds in a single lizard activity season. During each round, burrows were located and lizard presence or absence, fox digging and burrow condition were recorded. Out of 256 monitored lizard burrows, 12 were dug out by foxes. The data show that foxes actively seek to prey on pygmy bluetongue lizards. In several cases, the fox gave up before reaching the lizard. Dug out burrows were quickly abandoned by the surviving lizards and became filled in, reducing the supply of suitable burrows for the population. These data highlight the need for fox management around pygmy bluetongue lizard populations, especially if future management of the species involves relocation, as small newly established populations could be vulnerable to fox predation and secondary effects of burrow destruction.